(untitled) (Medico Legal Update, 2020)
Hemorrhoidal disease is one of most common anorectal disease and surgical hemorrhoidectomy remains one of most common operation in general surgery. The aim of the present study is to compare between conventional Milligan-Morgan hemorrhoidectomy and ligasure hemorrhoidectomy in treating patients with 3rd and 4th degree hemorrhoids. This randomized control trial was conducted at Alfayhaa teaching hospital during 2016 to 2018. The 3rd and 4th degree hemorrhoid patients (n=60, age 16-70 years) were randomly divided into two groups based on the surgical procedure, i.e. ligasure hemorrhoidectomy (n=30) and conventional hemorrhoidectomy (n=30). In ligasure hemorrhoidectomy, operative time, pain score on the 1st operative day and 1st week, duration of wound healing were 12.2 ± 03, 4.1 ± 05, 5.3 ± 02min and 3.1 ± 02, respectively. While in the conventional hemorrhoidectomy, it was 23.3 ± 02, 6.2 ± 03, 2.1 ± 09min and 4.4 ± 07, respectively. In ligasure hemorrhoidectomy 15 patients didn’t have blood loss, 10 patients had a mild blood loss and 5 patients had a moderate blood loss. While, in conventional hemorrhoidectomy all patients suffered from blood loss, i.e. 14 patients have mild blood loss and 11 patients have blood loss. In conventional hemorrhoidectomy postoperative bleeding, necrosis, residual disease and anal ____stenosis ___ were 19.2 ± 03 (p<0.001); 02.5 ± 01 (p<0.01); 08.9 ± 08 and 01.5 ± 01, respectively. While, in ligasure hemorrhoidectomy postoperative bleeding, necrosis and residual disease were reduced to 07.3 ± 07; 00.0 ± 00 and 04.9 ± 09, respectively. Anal ________stenosis ____ was found to be increased to 06.4 ± 06 as compared to the conventional hemorrhoidectomy. Ligasure hemorrhoidectomy is better than conventional hemorrhoidectomy in terms of less operative time,less intraoperative pain and less postoperative complication and earlier wound healing and return to daily work hence higher patient satisfaction.